EFFICACY OF COX-2 INHIBITOR ON CONCEPTION RATE IN BUFFALOES - NAVRANGE, P P; INGAWALE, M V; PAWSHE, C H; DESHMUKH, S G; MUNDE, V K (The Indian Journal of Animal Reproduction, 2023)
The present research was carried out to evaluate the efficacy of COX-2 inhibitor (flunixin meglumine) on conception rate in estrous synchronized buffaloes. Twenty four subestrous buffaloes which were non-exhibiting estrous symptom even 90 days after calving were randomly divided into two groups (n=12). The selected buffaloes from both the groups were synchronized with Ovsynch protocol, while buffaloes from Group-II were additionally administered with injection fluni.xin meglumine @ 1.1 mg /kg b. wt. intramuscularly on day 15 post insemination. The first service conception rate was 41.66 and 66.66 per cent in Group-I and Group-II, respectively.